The Influence of Viral Marketing, Celebrity Endorser, and Brand Awareness on Purchase Decisions on Make Over Cosmetic Products in Sidoarjo: Pengaruh Viral Marketing, Celebrity Endorser, Dan Brand Awareness Terhadap Keputusan Pembelian Pada Produk Kosmetik Make Over Di Sidoarjo - Istiqlaliyatul Kholiq; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine the effect of the Viral Marketing variable on the Purchase Decision, the influence of the Celebrity Endorser variable on the Purchase Decision, the influence of Brand Awareness on the Purchase Decision, and the influence of Viral Marketing, Celebrity Endorser, and Brand Awareness simultaneously affecting the Purchase Decision on Make Over Cosmetic Products. in Sidoarjo. This study uses a quantitative approach, by collecting data through a questionnaire. This study uses a purposive sampling technique. The sample used in this study was 100 respondents who used Make Over Cosmetics in Sidoarjo. The data analysis technique used to answer the hypothesis is multiple regression using the SPSS version 18.0 program. Based on the validity test of the valid questionnaire statement. The results of this study prove that the Viral Marketing variable has an effect on the Purchase Decision, the Celebrity Endorser variable has an effect on the Purchase Decision, and the Brand Awareness variable has an effect on the Purchase Decision. Viral Marketing, Celebrity Endorser, and Brand Awareness simultaneously affect the Purchase Decision on Make Over Cosmetics products in Sidoarjo.